Network Security Encryption Techniques for Reliablility Data Transmission on Password System - Norrozila, Sulaiman; Ng, Liang Shen; M. A., Ameedeen (2013)
The desire to transmit messages securely is not new. For centuries, community kept communication in secret. Nowadays, with the latest technology particularly the internet, vast amount of data transmit sensitive information but able to intercept easily if it is not encrypted before sending to the intended recipient. Encryption and decryption algorithm for secure communication depends on the algorithm while the internal structures of the robustness of the mathematics computation depend on the key it uses. A ciphertext can be transmitted openly across a communications channel. Because of its encrypted nature, eavesdroppers who may have access to the ciphertext will ideally be unable to uncover the message meaning. Only the intended recipient can decrypt the message to recover the plaintext for interpretation. An improved RSA algorithm using dynamic key from the private key from the receiver is proposed by dictating which key length to act according to bit length of an acceptable level key length for encryption and different lengths for complex algorithm, which increases the computing speed and increase the degree of security